Dynamics of Soil Moisture under Different Water Levels and Various Dosages of Organic Fertilizer - Subandi Nur; Suwarto Suwarto; Saparso Saparso; Heru Adi Djatmiko (JOURNAL OF TROPICAL SOILS, 2020)
The study aimed to determine the dynamics of soil moisture in various standing water levels and dosages of organic fertilizer. The experiment was arranged in a Completely Randomized Block Design (CRBD) with a 3 × 3 factorial treatment in 3 replicates. The first factor was 3 different water levels, namely 10 cm (T1), 20 cm (T2), and 30 cm (T3). The second factor was 3 levels of dosages of organic fertilizer, namely 0 g pot-1(P1), 35 g pot-1 (P2), and 70 g pot-1 (P3). The highest of soil moisture was obtained in the 10 cm water levels and 70 g organic fertilizer (T1P3) and the lowest in the 30 cm water levels and without organic fertilizer (T3P1). The highest infiltration rate was obtained in the 30 cm water levels and 70 g pot-1 organic fertilizer (T3P3), the 30 cm water levels and 35 g pot-1 organic fertilizer (T3P2), the 20 cm water levels and 70 g pot-1 organic fertilizer (T2P3), and the lowest in the combination of the 10 cm water levels and without organic fertilizer (T1P1). The highest capillary rate was obtained in the combination of the 30 cm water levels and 70 g organic fertilizer (T3P3) and the lowest in the combination of the 30 cm water levels and without organic fertilizer (T3P1).